Improved flotation separation of fine particles using hydrophobic silica nanoparticles as surface modifiers. Issue 6 (December 2021) - Kim, Sung-Man; Kim, Ilgook; Park, Chan Woo; Kim, June-Hyun; Yoon, In-Ho
Abstract: A new technology has been evaluated for its ability to selectively separate fine particles in cesium (Cs + )-contaminated soil using hydrophobic silica (HPOS) nanoparticles (NPs) as surface modifiers. Recent studies showed that separating Cs + -contaminated fine particles from soil can be an effective strategy for radioactive soil remediation due to the high Cs + fraction of fine particles. The influences of the silica type and dosage on separation efficiency and the interaction between silica NPs and fine particles were systematically examined. The results showed that fine particles attached to HPOS NPs can be separated in Cs + -contaminated soils by forming silica on the surface of fine particles due to van der Waals attraction, utilizing hydrophobicity to separate the fine particles from the soil. In separation experiments with soil mixtures, clay- and silt-sized fine particles that had been attached to HPOS NPs were separated by flotation due to gravity, and the separation efficiency improved when a mesh filter was added to exclude large particles. When 0.04 g HPOS NPs/g soil was applied, the attainable separation increased by 5-fold, and the maximum attainable separation increased from 20% without HPOS NPs to 99.5% when the NPs were used in column flotation tests. We also evaluated flotation-sieving separation for the selective separation of fine particles from Cs + -contaminated soil. After flotation separation, a high decontamination efficiency of approximately 60% was observed from the remaining unseparated fraction, which accounted for 73.4% of the total soil (initial fraction 72.5%). In conclusion, attaching HPOS NPs to fine particles in a flotation-sieving separation process significantly improved the separation of fine particles in Cs + -contaminated soil without surfactants, facilitating secondary waste disposal. Graphical Abstract: ga1 Highlights: Improved flotation was separated for fine particles in Cs soil by hydrophobic silica. Silica on the surface of fine particles was formed due to van der Waals attraction. The separation efficiency of silica-fine particles exceeded 99.5% by flotation. The high separation of fine particles resulted in high decontamination efficiency. This technology offers high-efficient and eco-friendly method without surfactant.